The Fifth Congress of the Portuguese Anthropological Association, September 2013 - Vesna Vučinić-Nešković (University of Belgrade, 2016)
The Fifth Congress of the Portuguese Anthropological Association (APA): "Anthropology in Counterpoint". Vila Real, Portugal: 8-11 September 2013.